ANALYSIS OF SERVICE QUALITY AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION IN BOGOR REGENCY - Syahrir (PROCURATIO: Jurnal Manajemen & Bisnis, 2023)
This study aims to investigate the quality of public services at the Population and Civil Registry Office of Bogor Regency. The research method used was quantitative with a descriptive statistical approach, involving 95 respondents selected through total sampling. The findings from the descriptive statistical test show that the quality of public services at the Bogor District Population and Civil Registration Office is generally considered "high and good." The conclusion of this study confirms that the quality of public services at the agency reflects the organization's positive efforts in meeting the community's needs and expectations.